Stabilitas Antioksidan Buah Kurma (Phoenix dactylifera L.) Pada Suhu Pemanasan Dengan Metobe ABTS - Sriwulan, Wieke (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2022)
Free radicals are compounds that are very dangerous for the body because they can attack and cause cell damage in the body, therefore antioxidant compounds are needed that can counteract the presence of these free radicals. One of the fruits that contain antioxidant compounds is dates (Phoenix dactylifera L.) which contain flavonoid compounds that act as antioxidants. The purpose of this study was to determine the antioxidant activity at heating temperatures of 400C, 500C, and 650C. The extraction method used in this study is the maceration method with 80% ethanol as solvent. Testing of antioxidant activity using the method of reducing free radicals, namely the ABTS method and using vitamin C as a comparison control to show antioxidant activity. ABTS is a method of determining antioxidant activity obtained from the oxidation of potassium persulfate with diammonium salt. Absorbance measurements were carried out using a UV-Vis spectrophotometer with a wavelength of 520 nm. Data analysis was carried out using linear regression equations to determine the IC50 value in the sample of dates (Phoenix dactylifera L.). The IC50 value indicates the antioxidant activity in a sample, namely the smaller the IC50 value, the higher the antioxidant in a sample. The results of data analysis using the Kruskal Wallis test obtained a significance value of 0.104 which indicates that > 0.05 which means there is no significant difference between each treatment group. From the results of the analysis data, it is known that there is no effect of heating temperature on the antioxidant stability of dates, this is also strengthened by the value of antioxidant activity in the linear regression equation where the value of antioxidant activity in each treatment group has an equally strong antioxidant activity value. based on the Blois classification. Keywords : Phoenix dactylifera L, Antioxidant and ExtractÂ